Problems of Primary Social Creative Forms and the Problem of the Origin of Music - Valiakhunova Feruza Ganijanovna (International Journal on Orange Technologies, 2021)
This article provides information about our national musical heritage, the role of our traditions in the educational process and spiritual life, and the subtle aspects of music education. Therefore, music can be a guarantee of conscious activity, productive work, sincere attitude and moderate mood. The more music is absorbed into our daily lives, the more enjoyable and meaningful Our Lives go. Music, which is considered one of the masterpieces created by our people, finds its expression to some extent in every sphere, chunanchi, Education, Labor and social relations. Murghak will enjoy the blessings of art, from the infant to the luminous elderly, will struggle to become brighter tomorrow.